The utilization of eco-friendly recycled powder from concrete and brick waste in new concrete: A critical review. (November 2020) - Tang, Qin; Ma, Zhiming; Wu, Huixia; Wang, Wan
Abstract: Recycled powder (RP) is the main by-product in the reclamation of construction and demolition (C&D) waste. A body of literature on the use of RP as supplementary cementitious materials (SCMs) in concrete is currently available, whereas a detailed review on the properties of RP concrete has been lacking until now. Considering that concrete and brick waste account for a large proportion of C&D waste and that other components have specific recycling paths, this paper provides a critical review on the utilization of recycled concrete powder (RCP) from concrete waste and recycled brick powder (RBP) from brick waste in new concrete. The preparation technology of RP and the properties of RP concrete are systematically reviewed; in addition, improvement methods and a benefit evaluation of RP concrete are further introduced. Based on statistical data that describe the activity index of RP and the compressive strength of RP concrete, the median diameter and replacement ratio of RP in concrete preparation should be below 30 μm and 30%, respectively. The use of RP improves the durability of concrete when the RP fineness is superior to the cement fineness. Increasing the RP fineness is an effective approach to improving the properties of RP concrete, and a CO2 -curing treatment of RCP is an eco-friendly modification method. Furthermore, the use of RP in concrete has good economic and environmental benefits. Therefore, one expects that this review helps the further use of RP in concrete.